Production of animal feed with improved nutrients from selected agro industrial wastes by solid state bioconversion - Ruqayyah, Tijani Iyabo Dasola (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
The use of abundant agro industrial residues, which have no direct importance to humans, for the production of animal feed via bioconversion indicates that it is quite feasible and economical for sustainable livestock production. This provides an effective strategy for meeting the feed demands particularly in emerging economies and also contributes to the management of the environmental nuisance created by their improper disposal. However, a major constrain in the bio-conversion of the agro industrial waste to animal feed is to isolate and grow locally sourced suitable white rot fungi that can degrades lignin while avoiding the degradation of polysaccharides. Hence, in this research, nutrients enriched animal feed production was targeted via solid state bioconversion of some selected agro industrial wastes. (rice husk, cassava peel and rice straw) using locally sourced white rot fungi. This was achieved by screening eleven white rot fungi sourced from Gombak forest, Selangor, Malaysia for their ligninolytic potential. Two isolates (M609RQY and M109RQY) emerged as potential strains on the basis of their ability to secrete the three lignin modifying enzymes (lignin peroxidase, manganese peroxidase and laccase ). These two isolates were then evaluated for their enrichment and ligninolytic enzyme ability on the three selected agro industrial wastes The isolate M609RQY identified as Panus I Lentinus tigrinus (IMI 398363) was found as the potential fungi and cassava peel stands out as the most potential substrate out of the three considered agro industrial wastes due to the enrichment in its nutritive value ( 40.81 % loss in lignin and 51.54% increase in protein content). Optimization of media constituents showed that wheat flour, MgS04 and particle size were the most influencing media constituents for the enrichment of cassava peel by the white rot fungi Panus tigrinus. Wheat flour at 4.3% (w/w), MgS04 at 0.45% and 1 mm particle size were found as optimum media constituents for the enrichment of cassava peel by the white rot fungi P. tigrinus. Under these optimum media conditions, protein content increased 'by 63.91% with lignin loss of 48.77%. The optimization study further showed that the optimum conditions for the bioconversion process were at a pH of 6, inoculum content of 6% (v/w) consisting of 1.04 mg biomass weight and moisture content of 70% (v/w). Under these conditions, the protein content further increased to 79.5% while about 46% degradation was obtained in the lignin content. Kinetic study of the developed process indicated six days as the optimal incubation period. The specific growth rate of P. tigrinus on cassava peel was estimated at 0.0452 day-1.The rate of protein formation was estimated to be 0.904 day-1 , specific rate of lignin degradation was estimated to be 0.3009 day"1 and specific rate of substrate loss was estimated at 0.8875 day-1 .The total sugar and the in vitro digestibility of cassava peel after bioconversion were both significantly (p > 0.05) enhanced than the control sample. The chemical composition of the validated product from tray bioreactor consist of crude protein, 8.69% with the presence of all the essential amino acids; crude fibre, 10.69; crude fat, 1.11 %; ash, 3.37%; lignin, 8.79%; cellulose, 12.36%; and hemicellulose,11.88%. It has a high in vitro dry matter digestibility, reduced HCN content below the minimum limit and has no cytotoxicity effect.